Sistem Pendukung Keputusan Penilaian Kesiapan UMKM Go-Digital Menggunakan Metode EDAS Berbasis Web - Niki Wulansari; Syaripah Nasriyah; Nurhayati Nurhayati; Yuyun Dwi Lestari (Universitas Islam Negeri Sumatera Utara, 2025)
Low levels of digital readiness and information technology literacy prevent many MSME from optimally utilizing digital platforms to support their business processes. This presents a significant challenge for accelerating digital transformation, particularly in Medan. This study aims to develop a web-based decision support system using the EDAS method to assess the level of readiness of MSME to go digital. This study employed a descriptive quantitative approach, with a sample of 15 MSME selected through a Likert-scale questionnaire. The data obtained were analyzed using the EDAS method to determine digital readiness scores based on established criteria and sub-criteria. The results showed that the system was able to provide a structured and objective assessment, with alternative A1 receiving the highest rating (0.5) and A9 the lowest (0.189). This study confirms that some MSME are still in the underprepared category and require training, mentoring, and digital capacity building support. The developed system can be a tool for the government and supporting institutions in mapping the level of digital readiness of MSME and developing more targeted strategies for accelerating digital transformation. Keywords: DSS, MSME, EDAS